Increasing Oil Production in Camelina sativa Engineered to Synthesize Unusual Lipids - Davis, Isabella; Alkotami, Linah; Durrett, Timothy P (My University, 2022)
Different Euonymus species naturally produce acetyl-triacylglycerol (acTAG) in their seed oil. AcTAG are unusual structures of the triacylglycerols (TAG) typically found in vegetable oil, and have lower freezing points and viscosity compared to regular vegetable oil. Seed oil containing AcTAG can be used as biodiesel, plasticizers, and other alternatives to petroleum-based products. AcTAG can be synthesized in Camelina sativa by expressing key enzymes from Euonymus and by using RNA interference (RNAi) to suppress competing camelina biochemical pathways. Previous observations of high acetyl-TAG camelina lines have shown an increase in overall TAG molecules, but lower fatty acid levels compared to wild-type seeds. It is hypothesized the decrease in overall fatty acid content is due to a limited amount of glycerol-3-phosphate (G3P) backbone. To increase G3P, C. sativa seeds were transformed to overexpress the gene that encodes glycerol-3-phosphate dehydrogenase (GPD1), which converts dihydroxyacetone phosphate (DHAP) to G3P. By increasing G3P synthesis, the fatty acid content is expected to increase to wild-type content or higher. C. sativa seeds were collected from third-generation homozygous transgenic lines for lipid analysis. These lines were analyzed in three or more replicates to measure the amount of AcTAG, TAG, and overall fatty acid per seed. The resulting data is expected to show increased fatty acid content closer to wild-type seeds. Higher fatty acid content using acTAG and TAG molecules can be used to decrease the number of plants needed to produce C. sativa oils and save agricultural space for farmers.
Keywords: Camelina sativa; biofuels; glycerol-3-phosphate dehydrogenase; lipid analysis; transgenic plants; USDA NIFA 2019-67032-29071